Efeito da salinidade sobre ganho de peso e Sobrevivência de tilápias vermelhas - Silva, Aline Gabrielle Gomes da (2019)
Tilapia is the fourth most important species of fish farmed in the world and the first in Brazil. Among the varieties now cultivated, Red Tilapia, also known as Saint Peter, has shown greater tolerance to salinity. The northeast region has saline areas and wells, which makes this species an alternative to increase aquaculture production. This dissertation is divided into two chapters. In the first one, the tolerance of Red Tilapia of different sizes to different salinities was evaluated. For this, post-larvae and juveniles of three size classes were submitted to tolerance test without acclimatization at salinity of 0 (control), 10, 20, 30 and 40 PSU (Practical Salinity Unit) and with acclimatization by increment of 0. , 5, 10 and 20 parts of salinity per day (PSU / day). In the test without acclimatization, fish exposed to salinity of 30 and 40 PSU showed weight decrease in the three size categories. 100% survival was observed for all groups up to 20 PSU, except T1 at salinity of 20 PSU. Multiple comparisons between survivals showed significant difference between T1 and T2 and T3 in salinity of 30 PSU and T1 and T2 compared to T3 in 40 PSU. When acclimatized, survival was higher in the larger size classes demonstrating a significant difference in survival between T1 compared with T2 and T3 by 5 PSU / day and T1 with T3 to 10 PSU / day. In both experiments the physicochemical parameters showed no significant variation between treatments p> 0.05. The second chapter evaluated the growth of Red Tilapia grown in different salinities. Thus, juveniles of Red Tilapia were cultivated for 93 days in salinities 0 (control), 10, 20, 30 and 40 PSU in 1000 liters boxes with aeration. Biometrics and analysis of water quality parameters were performed. Better growth was observed in salinities of 20, followed by 10 and 0 PSU. Salinities of 30 and 40 PSU presented lower weight gain in relation to the others. Low feed intake and good apparent feed conversion demonstrated good utilization of the food. This study provides important information on the tolerance, survival and performance of Red Tilapia grown in brackish and saltwater